PENGARUH CITA RASA, LOKASI DAN KUALITAS PELAYANAN DALAM MENENTUKAN LOYALITAS KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA OUTLET YO WES MIE SITUBONDO - Hamid, Zainol Hasan; Tulhusnah, Lusiana; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this research is to determine the influence of taste, location and service quality on consumer loyalty with purchasing decisions as an intervening variable at the Yo Wes Mie Situbondo outlet. The sampling technique used in this research is a saturated sample. The data analysis and hypothesis testing in this research used Structural Equation Models – Partial Least Square (PLS-SEM). The taste has a positive and insignificant effect on Purchasing Decisions, Taste has a positive and insignificant effect on Consumer Loyalty, Location has a significant positive effect on Purchasing Decisions, Location has an insignificant negative effect on Consumer Loyalty, Service Quality has a significant positive effect on Purchasing Decisions, Service Quality has an effect positive and insignificant effect on Consumer Loyalty, Purchase Decision has a significant positive effect on Consumer Loyalty, Taste has a positive and insignificant effect on Consumer Loyalty through Purchasing Decisions, Location has a significant positive effect on Consumer Loyalty through Purchasing Decisions, Service Quality has a significant effect on Consumer Loyalty through Decisions Purchase.